Inovasi Teknologi Perkerasan Jalan Beton Menggunakan Abu Vulkanik Dukono dan Kapur Sebagai Substitusi Semen - Mulya, Elfira Resti; Goraahe, Siti Hadija; Darwis, Fitro (Jurnal Serambi Engineering, 2026)
Road construction in Indonesia is increasing every year, including in Morotai, North Maluku. Low traffic can use rigid pavement technology or cement concrete pavement. Regional roads to connect various areas in the region such as industrial and tourism areas, agricultural areas and regional productivity. The purpose of this study is to determine the strength of concrete using Dukono volcanic ash and lime as a cement substitute as a technological innovation in concrete road pavement. This research method is an experimental method, where experimental testing is carried out in the Laboratory to determine concrete with a substitution of Dukono volcanic ash and lime for cement. Concrete strength tests carried out include compressive strength tests and split tensile strength tests. The results of the study showed that the concrete compression test with a variation of 15% volcanic ash and 5% lime had a compressive strength value of 351.45 kg / cm2, an increase in the compressive strength value of 16.5% from the planned concrete compressive strength, and for 20% ash and 5% lime an increase of 4.36%. For concrete road pavement, the use of volcanic ash and lime can be a solution for regional road pavement. Because at a percentage of 15% volcanic ash with 5% lime as a cement substitute, it results in an increase in concrete compressive strength of 16.5% at K-300.